Report on proposed new interior design of Belicious Boutique And Cafe at UM Land Showhouse, Jalan Maarof, 59000, Bangsar, Kuala Lumpur / Tuan Noor Azlina Tuan Hamzah - Tuan Hamzah, Tuan Noor Azlina (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design for Belicious boutiqueand cafe situated at Um Land Showhouse, Jalan Maarof, 59000 Bangsar, Kuala Lumpur. This proposed boutique and cafe is to attract tourist, mostly for those who come to Bangsar for traveling, holiday and shopping, at the same time to introduce the local brand of Belicious boutique to the Malaysians and also to generate Malaysia economy. The target market also for the local that comes to shopping at Bangsar. It is also focus at the Malaysian who is very interested with the local brand. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Belicious boutique and cafe. Sequence to that, the chosen character design for Belicious boutique and cafe is a modern design based on Belicious corporate image and at the same time would attract the customers with different image that they would only get in Belicious boutique. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend to the boutique, types of services offered, spaces to be concluded in the proposed area, nature of business and information about other fashion boutique and cafe that use the same system in management, as the proposed hotel. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.